2017
DOI: 10.1074/jbc.m116.763961
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role for Polycomb Group Protein Pcgf6 in Embryonic Stem Cell Maintenance and a Noncanonical Polycomb Repressive Complex 1 (PRC1) Integrity

Abstract: The Polycomb group (PcG) proteins have an important role in controlling the expression of key genes implicated in embryonic development, differentiation, and decision of cell fates. Emerging evidence suggests that Polycomb repressive complexes 1 (PRC1) is defined by the six Polycomb group RING finger protein (Pcgf) paralogs, and Pcgf proteins can assemble into noncanonical PRC1 complexes. However, little is known about the precise mechanisms of differently composed noncanonical PRC1 in the maintenance of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 53 publications
12
78
0
Order By: Relevance
“…Furthermore, we found that deletion of Pcgf1 resulted in the reduction of Ring1B and its associated histone mark H2AK119ub1 at Pcgf1 target genes. This result is similar to those observed for Pcgf6 −/− ES cells, suggesting a common molecular mechanism controlling Polycomb recruitment by Pcgf family in ES cells43. Of note, the occupancy of BcoR (another component of PRC1.1) at these targets is also decreased.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, we found that deletion of Pcgf1 resulted in the reduction of Ring1B and its associated histone mark H2AK119ub1 at Pcgf1 target genes. This result is similar to those observed for Pcgf6 −/− ES cells, suggesting a common molecular mechanism controlling Polycomb recruitment by Pcgf family in ES cells43. Of note, the occupancy of BcoR (another component of PRC1.1) at these targets is also decreased.…”
Section: Discussionsupporting
confidence: 86%
“…S2 and S3). These observations, together with our previous findings (19,20), strongly suggest that all PCGF family members except for Pcgf6 are dispensable for the self-renewal of ES cells.…”
Section: Pcgf3/5 Are Not Essential For Es Cell Self-renewalsupporting
confidence: 81%
“…To delete the region encoding the RING finger motif and introduce a frameshift, we designed two single guide RNAs (sgRNAs) specifically flanking exon 2 of the mouse Pcgf3 or Pcgf5 gene. Independent ES cell clones were isolated, and genomic deletions were confirmed by PCR with primers outside the expected cleavage site (19) (Fig. S1).…”
Section: Pcgf3/5 Are Not Essential For Es Cell Self-renewalmentioning
confidence: 99%
“…At molecular level, Pcgf6 null ES cells showed overexpression of genes involved in differentiation, especially in spermatogenesis and tend to differentiate towards endoderm when they formed EBs in vitro. Importantly, Pcgf 6 deletion in MEF did not have any effect on proliferation, suggesting that PCGF6 is important for stem cell-renewal but its function is dispensable in differentiated cells [339]. The genomic binding profile of PCGF6 is similar to TRXG activators and coincides to active chromatin marks.…”
Section: Ncprc13 and Ncprc15mentioning
confidence: 82%
“…CpG targeted ncPRC1.1 complexes are also active during pre-implantation development and play important role in establishing cellular plasticity of the early embryo [351]. Different ncPRC complexes, such as ncPRC1.6, can use independent targeting mechanism, and have a different, but just as important role in ES cell fate regulation [339]. The ncPRC1.6 complex does not harbor KDM2B or FBX10 subunits.…”
Section: Targeting Of Different Ncprc1 Complexesmentioning
confidence: 99%